Optimal ship hull via optimal parameterisation. Issue 3 (1st September 2016) - Peri, D.
Abstract : Numerical optimisation of a ship hull requires, like every shape design optimisation problem, the definition of a parametric expression of the object to be deformed. In this phase, some decisions are taken regarding the shape variability and the portion of the hull to be modified: the parameterisation of the hull is problem-dependent, with implications from the performances to be optimised (objective functions), and the right choice is not easy. In this paper, a parameterisation tool able to automatically select the optimal parameters selection and configuration, detecting together the most convenient portions of the hull to be modified and its optimal shape, is presented: the final solution is directly influenced by the characteristics of the specific optimisation problem. The total number of design parameters represents the only free choice about the parameterisation, while the areas on which the deformation is implemented, together with all the other parameters, are automatically selected without any further action by the designer.